Modeling congenital cataract in vitro using patient-specific induced pluripotent stem cells - Danni Lyu; Lifang Zhang; Zhenwei Qin; Shuang Ni; Jiayong Li; Bing Lu; Shengjie Hao; Qiaomei Tang; Houfa Yin; Zhijian Chen; Yong-Bin Yan; Junfeng Ji; et al. (npj Regenerative Medicine, 2021)
Abstract Congenital cataracts are the leading cause of childhood blindness. To date, surgical removal of cataracts is the only established treatment, but surgery is associated with multiple complications, which often lead to visual impairment. Therefore, mechanistic studies and drug-candidate screening have been intrigued by the aims of developing novel therapeutic strategies. However, these studies have been hampered by a lack of an appropriate human-disease model of congenital cataracts. Herein, we report the establishment of a human congenital cataract in vitro model through differentiation of patient-specific induced pluripotent stem cells (iPSCs) into regenerated lenses. The regenerated lenses derived from patient-specific iPSCs with known causative mutations of congenital cataracts (CRYBB2 [p. P24T] and CRYGD [p. Q155X]) showed obvious opacification that closely resembled that seen in patients’ cataracts in terms of opacification severity and disease course accordingly, as compared with lentoid bodies (LBs) derived from healthy individuals. Increased protein aggregation and decreased protein solubility corresponding to the patients’ cataract severity were observed in the patient-specific LBs and were attenuated by lanosterol treatment. Taken together, the in vitro model described herein, which recapitulates patient-specific clinical manifestations of congenital cataracts and protein aggregation in patient-specific LBs, provides a robust system for research on the pathological mechanisms of cataracts and screening of drug candidates for cataract treatment.